(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The use of innovative pedagogical technologies in the education of a foreign language and, in addition, mainly German language lessons, makes the lesson effective is an important factor in the organization and achievement of the intended goal. This through memorization of the topics covered in students, rapid assimilation of educational material, applying them consciously, learned words and phrases in speech is a skill and views are formed. This article is devoted to methods of improving the effectiveness of the use of information and innovative pedagogical technologies in foreign language education dedicated. Teaching students a foreign language using interactive methods in the article, issues of increasing interests, formation of communication are highlighted.